Pulmonary nocardiosis presenting as fungal ball-a rare entity - Ragini Tilak,1 D. Agarwal,2 T.K. Lahiri,2 Vijai Tilak.3 (The Journal of Infection in Developing Countries, 2008)
Pulmonary intracavitary infection caused by Nocardia is an opportunistic infection and is believed to be a rare entity. We describe a case report of a patient with culture positive Nocardia asteroides who presented with complaints of cough and expectoration with episodes of haemoptysis and dyspnoea. The diagnosis of nocardiosis was made by microscopic examination of the surgically resected portion of the lung and confirmed on culture.